THE MAIN TASKS OF TEACHING A STUDENT TO YOUTH LESSON IN RELATION TO SPECIALISTS (World Bulletin of Social Sciences, 2022)
We can confidently say that the academic discipline «Physical Culture and Sport» is one of the few academic disciplines that the negative consequences of quarantine have affected the most. This article describes the level of satisfaction of students in such difficult quarantine conditions.